Analysis of the Role of Socialization of Bpjs Program: A Study on Employee Nonparticipation in the Socialization Process - Akbar, Alvian; Yuanita; Yulia Anggraeni, Happy (Journal of Law, Politic and Humanities, 2025)
Socialization of the BPJS program is a strategic effort to increase understanding and participation of workers in the social security system. However, in practice, there are still employees who do not follow the socialization process, thus potentially hampering the effectiveness of the program. This study aims to analyze the role of the Social Security Organizing Agency (BPJS) in socializing the health insurance program for workers and to identify factors that cause workers' non-engagement. This research uses a qualitative approach with interview techniques, observation, and documentation analysis of employees and socialization organizers. The results showed that the role of BPJS in socializing the health insurance program has not been fully effective. The effectiveness of socialization depends on the communication strategy used, the level of involvement of company management, and the method of delivering information. Employee disengagement is caused by lack of access to effective information, lack of support from the company, and the perception that socialization does not have significant added value. Therefore, a more interactive, adaptive, and technology-based communication strategy is needed to increase employee involvement in the socialization of the BPJS program.